Invasive Aspergillus niger Is the Sole Etiological Agent for CSOM : A Clinical Case from Nepal - Ajay Kumar Chaurasiya; Rabindra Bhakta Pradhananga; Niranjan Prasad Sah; Basista Prasad Rijal; Bharat Mani Pokhrel; Santosh Dulal (Case Reports in Infectious Diseases)
Aspergillus causing chronic suppurative otitis media (CSOM) is rare in immunocompetent people; however, it can occur as a significant opportunistic pathogen in immunocompromised patients. Here, in our study, a 53-year-old diabetic patient having a history of CSOM visited the Department of Otorhinolaryngology-Head and Neck Surgery (ENT-HNS), Tribhuvan University and Teaching Hospital (TUTH), Nepal, in March 2016. Although he was on medication with an antibacterial ear drop from the last 10 days, his right ear was presented with otorrhea, pruritus, otalgia, aural fullness, hearing impairment, and tinnitus from the last 3-4 months. Preliminarily, otoscopy of the right ear revealed the presence of fungal mass. For further diagnosis, ear discharge was aseptically collected and sent to the laboratory to confirm the etiological agents. Findings of laboratory analysis indicated that Gram staining of aural discharge displayed pus cells with fungal spores but did not exhibit bacteria. Furthermore, potassium hydroxide (KOH) mount revealed the presence of fungal spores and septate hyphae with the characteristic of dichotomous branching. Culture in four different bacterial media (chocolate agar, blood agar, MacConkey agar, and Robertson’s cooked meat medium) has unveiled no bacterial growth. However, fungal growth was observed in both bacterial and fungal media. Thereafter, the fungal colony was investigated via a lactophenol cotton blue (LPCB) tease mount which displayed the structure of Aspergillus. Aspergillus niger was microbially conformed by specifically characterizing the specific phenotypic biseriate structure of phialides and the black-coloured conidia. For medication, the patient was treated with Candid Ear Drop with clotrimazole (1% w/v) plus lidocaine (2% w/v) for 4 weeks which successfully improved his condition.